Persepsi diabaikan orangtua memicu mahasiswa bunuh diri - Loo, Loora; Abidin, Zainal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
AbstractPerceived rejected by parents trigger suicide ideation. The suicide rate is high in Indonesia, especially among undergraduate students. Suicidal behavior is a way of solving negative problems which can also be a measure of student mental health. This study seeks to find out more about the factors that cause commit suicide. This method is an in-depth interview with three students who have suicidal ideation. The results of this study found several group factors in all subjects, namely dispotional vurnerability factors, generalization, additional stress, attention fixation, low stress tolerance threshold, and history of self-injury. It also found stress relieved from suicides with the perceived rejection. The threshold for tolerance to stress can be increased by a desire to achieve goals and an optimistic mind that the future will be better. Thus, suicidal ideation arises because of internal factors (maladaptive cognitive processes) and external factors (similar sources of stress).